Risk and Expected Returns of Private Equity Investments: Evidence Based on Market Prices - Jegadeesh, Narasimhan; Kräussl, Roman; Pollet, Joshua M. (Review of Financial Studies, 2015)
We estimate the risk and expected return of private equity using market prices of publicly traded funds of funds holding unlisted private equity funds and of publicly traded private equity funds participating directly in private equity transactions. We find that the market expects unlisted private equity funds to earn abnormal returns between –0.5% and 2% per year. In addition, private equity has a market beta close to one and a positive beta on the SMB factor. These listed funds exhibit greater systematic risk than an index based on the self-reported net asset value of unlisted private equity funds.